2021
DOI: 10.1177/1362361320984899
|View full text |Cite
|
Sign up to set email alerts
|

Can pictorial narration offer a solution to teacher training on the effective inclusion of students with autism spectrum disorder in low-resource settings? Investigation on knowledge and stigma change

Abstract: The main aim of this article is to explore whether pictorial narration could offer a solution to teacher training on the effective inclusion of students with autism spectrum disorder in a low-resource context in the Lao People’s Democratic Republic. For this purpose, pre- and post-training knowledge data were collected from 87 Laotian teachers who participated in teacher training using a pictorial narrative e-module called The Story of KhamdyTM. The teacher training included a half-day orientation workshop, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The result of table3 shows relationships between socio-demographic characteristics and trainers' knowledge were weak in all variable except the information variable with degree of significant school. While, a study conducts, about the impact of a program for teachers and their knowledge of the special pictorial narration for autistic children, show similarity in correlation result no significant between teacher knowledge about autism and their qualifications (0.204) and (0.244) for their experience by (19) . On the contrary, a study conducted had opposite result that was showed correlation between teacher's knowledge and their years of experience with autism (20).…”
Section: Recommendationmentioning
confidence: 96%
“…The result of table3 shows relationships between socio-demographic characteristics and trainers' knowledge were weak in all variable except the information variable with degree of significant school. While, a study conducts, about the impact of a program for teachers and their knowledge of the special pictorial narration for autistic children, show similarity in correlation result no significant between teacher knowledge about autism and their qualifications (0.204) and (0.244) for their experience by (19) . On the contrary, a study conducted had opposite result that was showed correlation between teacher's knowledge and their years of experience with autism (20).…”
Section: Recommendationmentioning
confidence: 96%